The influence of supervisor creative feedback environment on team creativity: The role of the ambidextrous learning and creative cognitive style - Liu, Shuwei; Zhang, Yawei; Liu, Yamei; He, Linyan; Xiao, Yuchun (Frontiers in Psychology, 2022)
The survival and success of organizations increasingly depend on creativity. A supervisor creative feedback environment is of special value in enhancing team creativity, but few studies have explored the relationship between the supervisor creative feedback environment and creativity and how it affects creativity. Based on feedback intervention theory, this paper explores the process mechanism and boundary conditions of supervisor creative feedback environment affecting team creativity from the perspectives of ambidextrous learning and team creative cognitive style.With 506 team members from 115 work teams in domestic enterprises as research samples, regression analysis was used to test the theoretical hypotheses. The results show that the feedback environment of supervisor creativity has positive affects on team creativity.ambidextrous learning mediates the relation between supervisor creative feedback environments and team creativity. Team creative cognitive style has a positive moderating effect on the the indirect relationship between a supervisor creative feedback environment and team creativity through ambidextrous learning. This study expands the application of feedback environment factors in the research field of team creativity,provides a theoretical framework for the influence of creative feedback environment on team creativity, and also provides theoretical support for managers to apply the management tool of supervisor creative feedback environment to organizational context to improve team creativity. Based on the research results, this paper puts forward corresponding management suggestions from the aspects of creating A supervisor creative feedback environment, attaching importance to team ambidextrous learning and making good use of creative cognitive style.